Strategi Promosi dan Komunikasi dalam Meningkatkan Partisipasi Masyarakat di TPQ Baitul Ghoni Kota Malang - Herman Silvia Isna Auladah; Qonita Shofia Niswah; Choirul Luthfi Muhammad; Budianto Langgeng; Rifa'i Ahmad Suzaki (IQRA : JURNAL PENDIDIKAN ISLAM, 2026)
Al-Qur'an Education Park (TPQ) is a non-formal Islamic educational institution that plays an important role in shaping children's religious character from an early age. However, the development of non-formal Islamic educational institutions still faces various challenges, particularly in promotion and communication, which affect community participation. This study aims to analyze the promotion and communication strategies implemented at TPQ Baitul Ghoni Malang City, identify the obstacles encountered, and formulate efforts to increase community participation. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation. Research informants consisted of the head of TPQ, teachers, parents, and community leaders. The results showed that the effectiveness of promotion and communication at TPQ Baitul Ghoni still faces several challenges, including limited utilization of digital media, ineffective internal communication coordination, low parental involvement through digital communication media, and the absence of a strong institutional branding strategy. Therefore, optimizing social media, strengthening internal communication, utilizing digital technology, and developing partnerships with the community are necessary to increase community participation in non-formal Islamic educational institutions.